1980
DOI: 10.1073/pnas.77.6.3201
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of chemical carcinogen-modified DNA by a DNA-binding protein.

Abstract: Using a filter binding assay, we have detected and partially purified a protein from human placenta that has a high affinity for N-acetoxy-2-acetylaminofluorene-modified double-stranded DNA (AAF-[3HJDNA) of bacteriophage 17. This protein has been partially purified from a 1 M NaC extract of a crude nuclear fraction by a combination of ion-exchange and nucleic acid affinity chromatography. With Although the excision repair of chemical damage clearly shares many features with the repair of UV-induced damage (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

1982
1982
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…According to its DNA-binding characteristics and substrate specificity, the DDB protein complex we identified appears to be different from the DDB proteins previously isolated from HeLa cells (16,34) or human placenta (10,25) and from other types of DNA-binding proteins such as histones and transcription factors. This protein complex also appears to belong to a different class from those described by Glazer et al (14), who found UV-inducible DNA-binding proteins in HeLa cells in the presence of either dactinomycin or cycloheximide and which have no specificity for UVdamaged DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to its DNA-binding characteristics and substrate specificity, the DDB protein complex we identified appears to be different from the DDB proteins previously isolated from HeLa cells (16,34) or human placenta (10,25) and from other types of DNA-binding proteins such as histones and transcription factors. This protein complex also appears to belong to a different class from those described by Glazer et al (14), who found UV-inducible DNA-binding proteins in HeLa cells in the presence of either dactinomycin or cycloheximide and which have no specificity for UVdamaged DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Complementation analysis of cells from patients with DNA repair disorders, such as xeroderma pigmentosum (XP), has indicated that the repair of bulky DNA lesions in mammalian cells is considerably more complex than that in bacteria. Several damage-specific DNA-binding (DDB) proteins in mammalian cells and tissues have been described (8-10, 25,34), but the physiological roles of these proteins have not been determined. Since isolation and cloning of the genes which encode mammalian DNA repair proteins have met with little success, specific information about the formation of DNA repair complexes (in particular those involved in the repair of bulky lesions, such as UV photoproducts) and their regulation in a stress-induced environment is not yet available.…”
mentioning
confidence: 99%
“…Several studies have revealed the existence of proteins in mammalian cells that bind specifically to DNA that has been damaged by chemical or physical agents. DNA damage recognition proteins (DRPs) have been reported for a growing list of DNA modifications, including certain cisplatin crosslinks (1,2), 1 ,N6-ethenoadenine (3), G:T mismatches (4), apurinic/apyrimidinic (AP) sites (5), N-acetyl-2-aminofluoreneguanine adducts (6), and ultraviolet light (UV)-induced photoproducts (7-9). The cellular function of these DRPs is currently unknown, but it is reasonable to speculate that some or all of these proteins may play roles in DNA repair (8,9), or in other biological activities related to the genotoxicity of the agent under investigation (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Damage recognition is an important component of the initial steps in the DNA repair process. A number of damage recognition proteins have been reported which bind to types of damaged DNA other than those containing psoralen plus UVA light induced interstrand cross-links (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). None of these proteins has been found to have DNA endonucleolytic activity but many have been hypothesized to play a role in the repair process.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins which specifically recognize and bind to DNA containing interstrand cross-links and which have been shown to play a role in the repair process have not been identified in mammalian cells. DNA binding proteins which recognize other types of DNA damage such as base modifications produced by either chemical or physical agents (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), bulky lesions (16)(17)(18), abasic sites (19,20), and mismatches in DNA (21), have been described in mammalian cells but whether these proteins play a role in the DNA repair processes is not clear, though has been suggested by the results of several of the studies.…”
mentioning
confidence: 99%